Diversity and Inclusion in Conservation: A Proposal for a Marine Diversity Network - Smith, Nicola S.; Côté, Isabelle M.; Martinez-Estevez, Lourdes; Hind-Ozan, Edward J.; Quiros, Angela L.; Johnson, Nathan; Green, Stephanie J.; Cornick, Leslie; Shiffman, David; Malpica-Cruz, Luis; Gleason Besch, Allison; Shiel-Rolle, Nikita (Frontiers in Marine Science, 2017)
Low diversity among scientists and practitioners is rampant in conservation. Currently, conservation professionals do not reflect the same diversity of perspectives and experiences of the world as the communities who bear the largest burden for implementing—or adverse consequences for failing to implement—conservation action. Acknowledging and describing the problem is important. But policies and programmes must also be put in place to correct it. Here, we highlight some measurable benefits of workforce diversity, and give an overview of some of the barriers to inclusion in marine conservation that help perpetuate low workforce diversity. Importantly, we underscore actions that both individuals and groups can take to alleviate such barriers. In particular, we describe the establishment of an online Marine Diversity Network, which conference participants proposed during a focus group meeting at the 4th International Marine Conservation Congress. The network will serve to bring together people from across the globe, from a variety of backgrounds, and from all career stages, to share knowledge, experiences and ideas, to provide and receive mentorship in marine conservation, and to forge new collaborations. Removing barriers to diverse participation requires coordinated, mindful actions by individuals and organizations. We hope that the proposed network and other actions presented in this paper find widespread support, and that they might serve both as inspiration and guide to other groups concerned with increasing diversity and inclusivity.